Esthesioneuroblastoma as an Unusual Cause for Dystopia. (24th September 2013) - Kamath, Vijna B.; Sowmya, V.; Ballal, Chandra Kumar; Mendonca, Norman
Abstract: Esthesioneuroblastoma, also known as olfactory neuroblastoma, is an uncommon malignant neoplasm arising from the olfactory epithelium in the roof of the nasal cavity. There are very few case reports published worldwide. The common presenting symptoms of Esthesioneuroblastoma are unilateral nasal obstruction (70%), epistaxis (50%), anosmia, rhinorrhoea, facial pain, headache, excessive lacrimation and rarely proptosis and visual disturbance. Apart from being locally aggressive, it metastasizes by haematogenous and lymphatic routes. We report an extremely rare case of esthesioneuroblastoma in a 20-year-old man with orbital involvement presenting as dystopia. This rare tumour should be considered in the differential diagnosis for young patients presenting to ophthalmic outpatient department with dystopia.